Selective processing of buildings and faces during working memory: the role of the ventral striatum. (22nd December 2014) - Haeger, Alexa; Lee, Hweeling; Fell, Juergen; Axmacher, Nikolai
Abstract The ventral striatum seems to play an important role during working memory (WM) tasks when irrelevant information needs to be filtered out. However, the concrete neural mechanisms underlying this process are still unknown. In this study, we investigated these mechanisms in detail. Eighteen healthy human participants were presented with multiple items consisting of faces or buildings. They either had to maintain two or four items from one category (low‐ and high‐memory‐load condition), or two from one category and suppress (filter out) two items from the other category (distraction condition). Striatal activity was increased in the distraction as compared with the high‐load condition. Activity in category‐specific regions in the inferior temporal cortex [fusiform face area (FFA) and parahippocampal place area (PPA)] was reduced when items from the other category needed to be selectively maintained. Furthermore, functional connectivity analysis showed significant reduction of striatal–PPA correlations during selective maintenance of faces. However, striatal–FFA connectivity was not reduced during maintenance of buildings vs. faces, possibly because face stimuli are more salient. Taken together, our results suggest that the ventral striatum supports selective WM maintenance by reduced gating of task‐irrelevant activity via attenuating functional connectivity without increasing task‐relevant activity correspondingly.